Identifying the Causal Effect of Alcohol Abuse on the Perpetration of Intimate Partner Violence by Men Using a Natural Experiment - Susan L. Averett; Yang Wang (Institute for the Study of Labor (IZA), 2014)
Intimate partner violence (IPV) is widespread among women, with substantial and long-lasting negative consequences. Researchers have documented a strong positive correlation between alcohol abuse and IPV. Yet prior researchers have struggled with the problem of the potential endogeneity of alcohol abuse. In this paper, we deal with this problem by exploring a unique instrumental variable - the September 11 terrorist attack (9/11) - in Wave III of the National Longitudinal Study of Adolescent Health. 9/11 was found in our data to lead to a significant increase in the frequency of alcohol abuse for respondents interviewed just after 9/11 compared to those interviewed before. Our OLS results indeed confirm earlier research of a strong positive correlation between alcohol abuse and IPV. However, the 2SLS results show no statistically significant effect of alcohol abuse on IPV. These results indicate that alcohol abuse might not have causal effects on IPV, and therefore have important policy implications.
Keywords: I12; I18; J12; 330; intimate partner violence; alcohol abuse; 9/11; instrumental variable